The glory of the invisible God: two powers in heaven traditions and early Christology - Orlov, Andrei A. (Jewish and Christian texts in contexts and related studies, 2019)
"Andrei Orlov examines early Christological developments in the light of rabbinic references to the "two powers" in heaven, tracing the impact of this concept through both canonical and non-canonical material. Orlov begins by looking at imagery of the "two powers" in early Jewish literature, in particular the book of Daniel, and in pseudepigraphical writings. He then traces the concept through rabbinic literature and applies this directly to understanding of Christological debates. Orlov finally carries out a close examination of the "two powers" traditions in Christian literature, in particular accounts of the Transfiguration and the Baptism of Jesus. Including a comprehensive bibliography listing texts and translations, and secondary literature, this volume is a key resource in researching the development of Christology."--